Anatomical and visual outcomes following ocriplasmin treatment for symptomatic vitreomacular traction syndrome - Singh, Rishi P; Li, Ang; Bedi, Rumneek; Srivastava, Sunil; Sears, Jonathan E; Ehlers, Justis P; Schachat, Andrew P; Kaiser, Peter K (British journal of ophthalmology, 2014)
Objective To evaluate the anatomical and visual outcomes of patients treated with ocriplasmin for the treatment of symptomatic vitreomacular adhesion (sVMA), including vitreomacular traction syndrome and macular holes. Design Retrospective, interventional, single centre, case series. Participants Patients with sVMA. Intervention Patients were treated with a single intravitreal injection of 0.125 mg ocriplasmin (Jetrea, Thrombogenics Inc, USA, Alcon/Novartis EU) with the reconstitution technique recommended by the manufacturer. Main outcome measures The primary study endpoint was the resolution of sVMA by spectral domain optical coherence tomography (SDOCT) at day 28. Secondary outcome measures included time to vitreous release, visual acuity (VA), changes in the optical coherence tomography (OCT) thickness and structure and macular hole closure rate. Results 17 patients were included in the study and resolution of vitreomacular adhesion (VMA) was verified by SDOCT in eight patients by day 28 (overall response rate of 47.1%, 8/17 eyes) with most patients experiencing VMA release by 7 days (41.2%, 7/17 eyes). Those who did not have VMA resolution showed no statistically significant change in VMA diameter as measured by horizontal and vertical 5-line raster scans at final follow-up (p=0.82 and p=0.75, respectively). The mean baseline Snellen VA was 20/49 and at final follow-up was 20/46 (p=0.59). The average central subfield thickness was 371 microns prior to treatment and 324 microns at final follow-up (range 191–767 microns, p=0.25). Patients meeting three of four positive predictors criteria (eg, no epiretinal membrane (ERM) at baseline, VMA diameter ≤1500 µm and phakic lens status) showed a response rate of 50.0% (seven of 14 patients); those meeting all four criteria (eg, younger than 65, no ERM at baseline, VMA diameter ≤1500 µm and phakic lens status) showed a response rate of 75.0% (three of four eyes). Transient outer segment ellipsoid zone loss was documented in seven patients and subretinal fluid presence following injection was noted in five patients. Four of the five patients with macular holes at baseline experienced resolution of their macular hole after injection. Conclusions This is the first study to quantify the extent of outer retinal changes seen in patients receiving ocriplasmin. Our initial experience with ocriplasmin shows a significant anatomical effect and is accompanied by transient changes in the outer retinal structures visualised by SDOCT.